Pengaruh Persepsi Kepercayaan dan Persepsi Keamanan Terhadap Pelaku Usaha Pada Penggunaan QRIS Sebagai Alat Pembayaran Digital Dalam Persepektif Bisnis Syariah : (Studi Pada UMKM di Bandar Lampung) - Mayang Saskia Anggraini; Erike Anggraeni; Nurhayati Nurhayati (Universitas 45 Surabaya, 2024)
Along with the development of financial technology, QRIS (Quick Response Code Indonesian Standard) has become a digital payment tool that is increasingly popular in Indonesia, including in Bandar Lampung. However, the adoption of QRIS in the context of sharia business faces challenges related to the perception of trust and security from business actors. This research aims to identify the influence of perceived trust and perceived security on business actors' decisions to use QRIS and its implications from a sharia business perspective. The formulation of the problem in this research is (1) How does the perception of trust influence business actors in using QRIS? (2) How does the perception of security affect business actors in using QRIS? (3) How do perceptions of trust and perceptions of security influence business actors' decisions, especially in sharia business?The aim of this research is to find out how perceptions of trust and perceptions of security influence the decisions of business actors, especially in Sharia Business. This research uses quantitative methods with a survey approach to collect data from business actors in Bandar Lampung. Data was collected through questionnaires that measured perceptions of trust, perceptions of security, and the decision to use QRIS. Data analysis was carried out using multiple linear regression to identify the influence of each variable as well as the interaction between perceived trust and perceived security.The research results show that perceived trust has a significant influence on business actors' decisions to use QRIS, with the higher the trust in QRIS, the greater the possibility of using this technology. Perception of security also has a significant influence; Business actors are more likely to adopt QRIS if they believe this system can protect data and transactions well. These two factors together influence business decisions, emphasizing the importance of improving security features and improving communications to increase QRIS adoption. In the context of sharia business, trust and security are very important, and business actors need assurance that QRIS complies with sharia principles and offers adequate data protection. QRIS providers are advised to clarify sharia compliance and security features to increase adoption among sharia business actors.